(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
To training the association of polycystic ovaries with p53 and 72 polymorphisms in the population of female infertility in central Karbala and to search for possible interaction with the polymorphism. The Iraqi environment was suffered from acts of profanation by due to wars in Iraq, since 1990 and after 2003, An enormous number of damages and deaths were affected by destructive chemicals and radioactive resources. These events resulted in either cancer or infertility. Infertility is one of the medical, social and psychological burdens in Iraqi society. After 12 months or more of failure to a clinical pregnancy lead to a regular unprotected sexual intercourse.